STUDENTS’ READING MOTIVATION, READING ACHIEVEMENT AND PARENTS’ ECONOMIC STATUS - Rahmi Aulia; Machdalena Vianty; Diemroh Ihsan (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2014)
Abstract: The aims of this study were to find out whether or not there were significant correlations among each aspect of parents’ economic status, students’ reading motivation, and reading achievement. In addition, the contributions of parents’ economic status and reading motivation to reading achievement were also investigated. One hundred twenty students were selected as the sample by using a purposive sampling technique. The data were collected by using a parents’ socioeconomic questionnaire, a reading motivation questionnaire, and a reading test. Pearson product moment correlation and multiple regression analyses were applied to analyze the data. The correlation analysis showed that the aspects of parents’ economic status: parental income (r=.546), property (r=.294), and facilities at home (r=.535) were significantly correlated with reading achievement. However, only parental income (29.8%) and facilities at home (4.8%) gave significant contribution to reading achievement. Significant correlations also existed between parental income (r=.394); property (r=.250); facilities at home (r=.343), and reading motivation, but only parental income gave significant contribution (15.5%). All the aspects of students’ reading motivation were also significantly correlated with reading achievement, but only self-efficacy (18.15%) and competition (7.1%) that contributed significantly. The results of this study confirm the important role of parents’ economic status in their children’s reading motivation and reading achievement. Key words:parents’ economic status, students’ reading motivation, students’ reading achievement